Аналіз вибуху ядерного реактора Чорнобильської АЕС у квітні 1986 р. за допомогою тензорних рівнянь - Matsuki, Yoshio; Bidyuk, Petro I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2017)
This research analyzes the process of the explosion of the reactor core of Chernobyl nuclear plant in April 1986, using the tensor equations. These tensor equations show a movement of a vector in the three dimensional curvature coordinates of time, water flow, and void. The equations shows that this vector moves along the geodesic in the curvature coordinates, which is described by fundamental tensor (gµν), Christoffel symbol (Γαµνσ) and Ricci tensor (Rµν), where µ, ν, σ, α are suffixes that indicate the coordinates. The solution of the tensor equations shows that the geodesic of the vector has a singular point, which describes a turning point of the reactor core from the normal operation to the explosion, which we reported in our previous articles [1, 2].